Treatment of pediatric fistula-in-ano—Sphincter-sparing non-cutting seton placement as the future treatment of choice? - Besendörfer, Manuel; Langer, Laurin; Carbon, Roman; Weiss, Christel; Müller, Hanna; Diez, Sonja (Frontiers in Surgery, 2023)
Background. Therapeutic principles of fistula in ano (FIA) are lacking evidence-based consensus on treatment options. Non-cutting, sphincter-sparing options have not been published in infancy and childhood FIA. Patients and Methods. We are presenting retrospective data on FIA treatment with non-cutting seton placement between 2011 and 2020. Data was collected based on medical records and was complemented by patients’ contact for follow-up analyses between November 2021 and October 2022. Data were analyzed regarding the outcome variables of recurrent FIA and recurrent perianal abscess. Furthermore, outcomes in different age groups were compared (<1/ 1.5-12 years of age). Results. Treatment duration with non-cutting seton was at a median of 4.6 months and was not associated with recurrent FIA (p=0.8893). Overall recurrence rate of FIA within an observation time of 9 months post-surgically was at 7% (n=3/42) and recurrent FIA was only seen in infancy, whereas recurrent perianal abscess was mainly observable in children (n=2, p=0.2132). Comparison of age groups revealed no significant differences. Of 42 included patients, 37 responded in the follow-up-analysis, resulting in a response rate of 88% with a median follow-up time of 4.9 years. Fecal incontinence was post-surgically only seen in two patients, who were diagnosed prior to surgery and symptoms remained unchanged. Conclusions. Non-cutting seton placement might be a promising option in treatment of FIA in infancy and childhood. Perioperative settings like duration of placed seton and antibiotic treatment have to be discussed in further prospective, enlarged-population based studies.